2015
DOI: 10.1007/s10578-015-0577-4
|View full text |Cite
|
Sign up to set email alerts
|

Relating Worry and Executive Functioning During Childhood: The Moderating Role of Age

Abstract: The associations between worry and executive functioning across development have not been previously explored. Examining the interrelationships between these variables in childhood may further elucidate the cognitive nature of worry as well as its developmental course. Hypotheses predicted that difficulties with executive functioning would correlate with child worry; based on extant literature, age-related hypotheses were proposed for particular aspects of executive functioning. Children (N = 130) participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…The current findings extend the literature by indicating that the BRIEF is sensitive to internalizing problems such as anxiety and depression afflicting adolescents in the community. This is consistent with recent work, including previously mentioned studies documenting associations between BRIEF scores and self-reported worry severity (Geronimi et al, 2016), and anxiety (Affrunti & Woodruff-Borden, 2015) among children, and depressive symptoms among adolescents (Wante et al, 2017). The implications of these findings are significant, suggesting that elevations in scores on the BRIEF should alert clinicians to thoroughly screen for internalizing—in addition to externalizing—symptoms in their patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current findings extend the literature by indicating that the BRIEF is sensitive to internalizing problems such as anxiety and depression afflicting adolescents in the community. This is consistent with recent work, including previously mentioned studies documenting associations between BRIEF scores and self-reported worry severity (Geronimi et al, 2016), and anxiety (Affrunti & Woodruff-Borden, 2015) among children, and depressive symptoms among adolescents (Wante et al, 2017). The implications of these findings are significant, suggesting that elevations in scores on the BRIEF should alert clinicians to thoroughly screen for internalizing—in addition to externalizing—symptoms in their patients.…”
Section: Discussionsupporting
confidence: 93%
“…It focuses on a large, diverse community sample of adolescents. While previous studies of the BRIEF often included only parent-report (Affrunti & Woodruff-Borden, 2015; Geronimi et al, 2016) or parent-report and teacher-report (Toplak et al, 2009), this study included both parent-report and adolescent-report on the BRIEF and on all outcome measures. Another strength of this study is that we controlled for IQ in all analyses, minimizing an important potential confound.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies examined the relationship between worry and working memory in youth (see Table 2). As mentioned above, one study showed that poor working memory was associated with high worry in children (7-12-year-olds), as measured with the BRIEF questionnaire (Geronimi et al 2016). However, age moderated this relationship with the effect strongest in younger children (i.e.…”
Section: Working Memorymentioning
confidence: 94%
“…The BRIEF, composed of eight subscales, captures different aspects of executive functions such as inhibition, shifting, emotion control, initiating, working memory, planning, organisation, and monitoring. One study showed that deficits on all eight dimensions of the BRIEF were associated with high worry in 7-12-year-old children (Geronimi et al 2016). Furthermore, age moderated this relationship for the executive domains of planning, working memory, and monitoring, whilst shifting, inhibition, and emotion control had a more stable association with worry across ages.…”
Section: Attentional Controlmentioning
confidence: 99%
See 1 more Smart Citation